2000
DOI: 10.1097/00000372-200006000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic Angioleiomyoma

Abstract: We describe two cases of pleomorphic angioleiomyoma. In one case, a 46-year-old man presented with a single nodule on his scrotum of 1 year's duration, and in another, a 38-year-old woman presented with a single nodule on her right knee of 1 year's duration. In both cases, histopathologic examination showed a well-circumscribed nodule composed of smooth muscle and numerous veins and capillaries. Contrary to the ordinary angioleiomyoma, marked nuclear pleomorphism was noted. Although mitoses were rare, immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…Previously described cases show bizarre cytologic changes in the background of a cirsoid aneurysm (arteriovenous hemangioma) or capillary‐type hemangioma. Since its original description, a further three cases were reported in the German literature by Kutzner et al 2 Histologically similar vascular lesions with pleomorphic stromal cells probably representing further examples of SH 3 have been described as pleomorphic angioleiomyoma 4–7 cutaneous angiomyolipoma with pleomorphic changes 8 and bizarre angiomyomas of soft tissue 9 . Herein, we describe an additional two cases of this distinctive but poorly recognized entity.…”
mentioning
confidence: 99%
“…Previously described cases show bizarre cytologic changes in the background of a cirsoid aneurysm (arteriovenous hemangioma) or capillary‐type hemangioma. Since its original description, a further three cases were reported in the German literature by Kutzner et al 2 Histologically similar vascular lesions with pleomorphic stromal cells probably representing further examples of SH 3 have been described as pleomorphic angioleiomyoma 4–7 cutaneous angiomyolipoma with pleomorphic changes 8 and bizarre angiomyomas of soft tissue 9 . Herein, we describe an additional two cases of this distinctive but poorly recognized entity.…”
mentioning
confidence: 99%
“…Kawagishi et al [6] and J. A. Martínez et al [7] have reported cases of pleomorphic angioleiomyomas in the subcutis of lower extremities and scrotum.…”
Section: Discussionmentioning
confidence: 99%
“…They are solid or capillary, cavernous, and venous. 4,15 A pleomorphic variant has recently been described by Martinez et al 16,17 This is a benign variant containing many bizarre, pleomorphic cells that simulate malignancy. Although the most common form is the solid subtype, which is three times more commonly seen in females and predominately affects the legs, the cavernous type is four times more commonly seen in males and principally affects the upper limb and head.…”
Section: Discussionmentioning
confidence: 99%